METODOLOGIA DOS LIMIARES HEDÔNICOS VARIANDO MAIS DE UM ESTÍMULO: APLICAÇÃO NA REDUÇÃO DE CLORETO DE SÓDIO EM BISCOITO SALGADO - Araujo, Cirila Ionara Almeida (2020)
The hedonic threshold methodology (HTM), by calculating the compromised acceptance threshold (CAT) and the hedonic rejection threshold (HRT), allows to identify the beginning of the reduction of acceptance and sensory rejection of foods, varying the inten